THE GRAMMATICAL ERRORS OF SPOKEN ENGLISH PRODUCED BY THE FIRST SEMESTER STUDENTS OF INTENSIVE COURSE - El-Sulukiyyah, Ana Ahsana (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This study carried out the grammatical errors of spoken English produced by the first semester students of English Education Study Program in Intensive Course lecture focusing in speaking subject. The students are natively Javanese and had studied English including grammar for several years. There were 44 students in this class and had 6 weeks meeting with some various spoken performances such as role playing and prepared talk. From the analysis of the spoken errors made, it was found there were three common errors produced like subject-verb agreement, noun changes (singular to plural), and the use of “to be”. These errors produced because of the influence of their mother tongue and their misuderstanding of using the correct grammar. Regular performance correction gave much help to develop students’ understanding in using good grammatical order in spoken English activities.